A low-energy consumption hydrogen production and co-production of olefins solid oxide electrolytic cell and preparation method thereof
By using Sr1.95Fe1.3Co0.2Mo0.5O6-δ as anode and cathode materials in solid oxide electrolytes, the performance problems of electrolytic cell caused by low anode catalytic activity are solved, and higher stability and resistance to carbon deposits are achieved.
Patent Information
- Application Number
- CN202210793404.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-07
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-07-07
AI Technical Summary
In existing solid oxide electrolytic cells, the poor performance of the electrolytic cells is caused by low anode catalytic activity.
Sr1.95Fe1.3Co0.2Mo0.5O6-δ was used as the anode and cathode material, and LSGM was used as the solid electrolyte to prepare a solid oxide electrolyte with Sr1.95FCM0.2-LSGM-Sr1.95FCM0.2 structure by screen printing.
The activation activity of ethane conversion is improved, the stability and carbon deposition resistance of the electrolytic cell are enhanced, and the performance has no significant attenuation after 20 hours, and the electrode microstructure remains intact.
Smart Images

Figure CN115287684B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solid oxide electrolytic cells, and in particular to a low-energy consumption hydrogen production and co-production of olefins solid oxide electrolytic cell and a preparation method thereof. Background Art
[0002] Solid oxide fuel cells (SOFC) are one of the most important technologies for clean and efficient energy production. By designing and transforming the battery into a symbiotic SOFC for ethylene and electricity, ethylene can be obtained while generating electricity; using the solid oxide electrolysis cell SOEC of the reverse process of the battery to co-electrolyze C2H6-H2O, ethane is electrolyzed at the anode to obtain ethylene, and water is electrolyzed at the cathode to obtain hydrogen. Both symbiotic SOFC and SOEC can improve the low selectivity and severe carbon deposition problems of traditional ethylene preparation. The progress of the reaction can be regulated by controlling the current potential, so that it is expected to achieve a high yield of ethane converted into ethylene.
[0003] SOEC is the reverse process of SOFC, which can use renewable electricity to convert electricity into fuels and chemicals. Its advantages are long life, wide application, low cost, etc., so it has great potential for practical application.
[0004] In oxygen ion conductor SOECs, the electrochemical oxidation of C2H6 to C2H4 involves key steps: first cleavage of the C–H bonds in C2H6, followed by selective coupling of C–C bonds to generate C2H4 via a gaseous electrochemical process in the porous anode. 2- The electrochemical pump converts O 2- The transport from the cathode to the anode is actually a process of providing active oxygen species for C2H6 activation and oxidation under a suitable catalyst electrode. 2- The electrochemical oxidation of C2H6 is also a charge balance process, and O 2- The conversion to the active interface in the anode will involve different types of oxygen, including O 2- and O - ions. The active metal-oxide interfaces at the nanoscale are ideal for generating these oxygen species, especially those in the form of O - These active oxygen species are the key active free radicals that activate C2H6 at the metal-oxide interface. Under suitable interfacial catalysts, O 2- The electrochemical pump continuously oxidizes C2H6 to generate C2H4. The active oxygen species electrochemical pump can also oxidize and remove the carbon deposits produced on the porous anode, thereby improving the resistance to carbon deposition during the cracking of C2H6. The oxygen-containing molecules (such as gaseous O2, H2O or CO2) in the cathode form O under the applied potential. 2-The advantage of co-electrolysis is that the oxygen species produced by the electrolysis of H2O to H2 or the electrolysis of CO2 to CO are directly utilized and transferred to the anode for selective oxidation of C2H6 to C2H4.
[0005] Double perovskite Sr2Fe 1.5 Mo 0.5 O 6-δ As a mixed ion-electron conductor, SFM has excellent oxygen ion and electron conductivity properties, and its larger three-phase boundary is conducive to accelerating the electrochemical reaction in hydrocarbon fuels. However, the catalytic activity of SFM materials still needs to be further improved.
[0006] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0007] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a low-energy consumption solid oxide electrolytic cell for producing hydrogen and co-producing olefins and a preparation method thereof, aiming to solve the problem of poor performance of the existing solid oxide electrolytic cell due to low anode catalytic activity.
[0008] The technical solution of the present invention is as follows:
[0009] A low-energy consumption hydrogen production and co-production of olefins solid oxide electrolysis cell, comprising a solid electrolyte and an anode and a cathode located on both sides of the solid electrolyte, wherein the materials of the anode and the cathode are Sr 1.95 Fe 1.3 Co 0.2 Mo 0.5 O 6-δ .
[0010] In the low-energy consumption hydrogen production and olefin co-production solid oxide electrolysis cell, the material of the solid electrolyte is LSGM.
[0011] A method for preparing a low-energy consumption hydrogen production and olefin co-production solid oxide electrolytic cell, comprising the steps of:
[0012] An anode and a cathode are provided, wherein the materials of the anode and the cathode are both Sr 1.95 Fe 1.3 Co 0.2 Mo 0.5 O 6-δ ;
[0013] The anode and cathode are printed on both sides of the solid electrolyte, and the anode and cathode are connected via a wire to obtain the low-energy consumption hydrogen production and co-production of olefins solid oxide electrolysis cell.
[0014] The method for preparing a low-energy consumption hydrogen production and co-production of olefin solid oxide electrolytic cell, wherein the Sr1.95 Fe 1.3 Co 0.2 Mo 0.5 O 6-δ The preparation comprises the steps of:
[0015] Co(NO3)2, Sr(NO3)2, Fe(NO3)3·9H2O and (NH4)6Mo7O were added according to the set stoichiometric ratio. 24 4H2O is dissolved in an aqueous solution containing nitric acid to completely dissolve the nitric acid to obtain a first mixed solution;
[0016] According to n (CA) :n (EDTA) :n (total ions) =1.5:1:1 ratio, sequentially adding citric acid and ethylenediaminetetraacetic acid to the first mixed solution, stirring evenly, to obtain a second mixed solution;
[0017] Adding ammonia water to the second mixed solution, adjusting the pH value of the second mixed solution to 7-7.5, and completely dissolving the ethylenediaminetetraacetic acid to obtain a third mixed solution;
[0018] The third mixed solution is stirred to form a metal complex solution, and then heated to dryness at 200° C. until burned, and the precursor is collected;
[0019] The precursor is moved into a crucible for calcination to obtain the Sr 1.95 Fe 1.3 Co 0.2 Mo 0.5 O 6- δ.
[0020] Beneficial effect: The present invention converts the double perovskite material Sr with the best electrochemical performance into 1.95 Fe 1.3 Co 0.2 Mo 0.5 O 6-δ (Sr 1.95 FCM0.2) was used as a symmetrical electrode of a low-energy hydrogen production and olefin co-production solid oxide electrolyzer SOEC. It was found that the electrolyzer could not only improve the activation activity of ethane conversion, but also improve the stability and resistance to carbon deposition. After the electrolyzer had been working for 20 hours, there was no significant attenuation in performance, the electrode microstructure remained intact, and there was no obvious carbon deposition. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 a is Sr 1.95 SEM micrographs of the cross-section of FCM0.2 anode and LSGM electrolyte, b is Sr 1.95Amplified SEM image of FCM0.2 anode, c is Sr 1.95 High magnification TEM image of FCM0.2 powder sample, d is the Sr after reduction 1.95 High-magnification TEM image of FCM0.2 powder sample.
[0022] Figure 2 a is Sr after reduction 1.95 HAADF image of FCM0.2 powder sample, b is the EDS analysis diagram of Fe, c is the EDS analysis diagram of Co, d is the EDS analysis diagram of Sr, e is the EDS analysis diagram of Mo and f is the EDS analysis diagram of O.
[0023] Figure 3 a in the figure is Sr before and after reduction 1.95 The XPS spectrum fitting analysis of O1s of FCM0.2; b is the Sr 1.95 Co 2p core-level spectrum of FCM0.2 and its fitting results analysis diagram; c is the Sr 1.95 The core-level spectrum of Fe 2p of FCM0.2 and its fitting results analysis; d is the Sr 1.95 The core-level spectrum of Mo 3d of FCM0.2 and its fitting results analysis diagram.
[0024] Figure 4 For Sr 1.95 FCM0.2 / LSGM / Sr 1.95 IV curve of FCM0.2 SOEC in single electrolysis of 20% H2O.
[0025] Figure 5 a is Sr 1.95 FCM0.2 / LSGM / Sr 1.95 Impedance spectrum of FCM0.2 SOEC electrolyzing 20% H2O at 650-750℃ with 1.3V applied, b is Sr 1.95 FCM0.2 / LSGM / Sr 1.95 Impedance spectra of FCM0.2 SOEC electrolyzing 20% H2O at different voltages at 700℃.
[0026] Figure 6 a is Sr 1.95 FCM0.2 / LSGM / Sr 1.95 Stability curves of FCM0.2 SOEC at different voltages for single electrolysis of 20% H2O at 700℃; b is Sr 1.95 FCM0.2 / LSGM / Sr 1.95 Stability curve of FCM0.2 SOEC at 700℃ and 1.1V for single electrolysis of 20% H2O.
[0027] Figure 7 a is Sr 1.95 FCM0.2 / LSGM / Sr 1.95 SEM image of the anode surface of FCM0.2 SOEC after testing at 700℃ and 1.1V constant voltage for 20 hours; b is Sr 1.95 FCM0.2 / LSGM / Sr 1.95 SEM image of the anode-electrolyte interface of FCM0.2 SOEC after testing at 700°C and 1.1V constant voltage for 20 hours.
[0028] Figure 8 Sr 1.95 FCM0.2 / LSGM / Sr 1.95 IV curve of FCM0.2 SOEC in co-electrolysis of 20% H2O-C2H6.
[0029] Fig. 9 Sr 1.95 FCM0.2 / LSGM / Sr 1.95 Comparison of IV curves of FCM0.2 SOEC at 750℃ when single electrolysis of 20% H2O and co-electrolysis of 20% H2O-C2H6.
[0030] Fig.10 a is Sr 1.95 FCM0.2 / LSGM / Sr 1.95 Impedance spectrum of FCM0.2 SOEC at 650-750℃ with 1.3V applied for co-electrolysis of 20% H2O-C2H6; b is Sr 1.95 FCM0.2 / LSGM / Sr 1.95 Impedance spectra of FCM0.2 SOEC co-electrolyzing 20% H2O-C2H6 at different voltages at 700℃.
[0031] Fig.11 (a) is a graph showing ethane conversion rate when the symbiotic SOFC is operating at 650-750°C and a voltage of 1.3V is applied to the SOEC; (b) is a graph showing ethylene selectivity when the symbiotic SOFC is operating at 650-750°C and a voltage of 1.3V is applied to the SOEC.
[0032] Fig.12 a is Sr 1.95 FCM0.2 / LSGM / Sr 1.95 Stability curves of FCM0.2 SOEC at different voltages for co-electrolysis of 20% H2O-C2H6 at 700℃; b is Sr 1.95 FCM0.2 / LSGM / Sr 1.95Stability curve of FCM0.2 SOEC at 700℃ and 1.1V for co-electrolysis of 20% H2O-C2H6.
[0033] Fig.13 a is Sr 1.95 FCM0.2 / LSGM / Sr 1.95 SEM morphology of the anode surface of FCM0.2 SOEC after testing at 750℃ and 0.7V constant voltage for 20h; b is Sr 1.95 FCM0.2 / LSGM / Sr 1.95 Raman spectrum of the SOEC anode side of FCM0.2 after testing at 750℃ and 0.7V constant voltage for 20h. DETAILED DESCRIPTION
[0034] The present invention provides a low-energy consumption hydrogen production and co-production of olefins solid oxide electrolysis cell and a preparation method thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0035] The present invention provides a low-energy consumption hydrogen production and co-production of olefins solid oxide electrolysis cell, which comprises a solid electrolyte and an anode and a cathode located on both sides of the solid electrolyte, wherein the material of the anode and the cathode are Sr 1.95 Fe 1.3 Co 0.2 Mo 0.5 O 6-δ In this embodiment, the material of the solid electrolyte is LSGM, i.e. La 0.8 Sr 0.2 Ga 0.8 Mg 0.2 O 3-δ .
[0036] In some embodiments, a method for preparing a low-energy consumption hydrogen production and co-production of olefins solid oxide electrolysis cell is also provided, which comprises the steps of: providing an anode and a cathode, wherein the materials of the anode and the cathode are both Sr 1.95 Fe 1.3 Co 0.2 Mo 0.5 O 6-δ The anode and cathode are printed on both sides of the solid electrolyte, and the anode and cathode are connected by a wire to obtain the low-energy consumption hydrogen production and co-production of olefins solid oxide electrolysis cell.
[0037] In this embodiment, the Sr 1.95 Fe 1.3 Co 0.2 Mo 0.5 O6-δ The preparation comprises the steps of: mixing Co(NO3)2, Sr(NO3)2, Fe(NO3)3·9H2O and (NH4)6Mo7O according to a set stoichiometric ratio. 24 ·4H2O is dissolved in an aqueous solution containing nitric acid to completely dissolve it, thereby obtaining a first mixed solution; (CA) :n (EDTA) :n (total ions) =1.5:1:1, sequentially adding citric acid and ethylenediaminetetraacetic acid to the first mixed solution, stirring evenly, to obtain a second mixed solution; adding ammonia water to the second mixed solution, adjusting the pH value of the second mixed solution to 7-7.5, so that the ethylenediaminetetraacetic acid is completely dissolved, to obtain a third mixed solution; stirring the third mixed solution to form a metal complex solution, and then heating and evaporating at 200° C. until burning, collecting the precursor; transferring the precursor into a crucible for calcination to obtain the Sr 1.95 Fe 1.3 Co 0.2 Mo 0.5 O 6-δ .
[0038] The present invention is further explained below by specific embodiments:
[0039] The present invention has previously studied the modification of the double perovskite matrix SFM and finally optimized the best A-vacancy and B-site Co-doped Sr 1.95 FCM0.2 anode material. It has been widely proven that the in-situ precipitation of metal nanoparticles on an oxide matrix under a reducing atmosphere can greatly improve the catalytic conversion of C2H6 to C2H4. It is generally believed that the formation of a strongly interacting metal-oxide interface promotes catalytic conversion, and the metal nanoparticles directly embedded in the porous oxide show better high-temperature stability and resistance to carbon deposition. The strong metal-oxide interaction at the unique nanoscale interface structure is very beneficial to the transfer of oxygen species, especially the oxygen species present in the form of oxygen ions in the present invention. It is expected that these active oxygen species can electrochemically activate and oxidize C2H6 in situ, and the active oxygen present at the metal oxide interface of the cathode can also remove carbon deposition.
[0040] So in the invention, we choose Sr 1.95 FCM0.2 was used as both the anode and cathode of SOEC, and the oxygen ion conductor LSGM was used as the electrolyte. Sr 1.95 FCM0.2-LSGM-Sr 1.95 FCM0.2 structure for the study of single electrolysis of H2O, and co-electrolysis of H2O-C2H6 with electrochemical oxidation of C2H6 to chemicals at the anode and simultaneous electrolysis of H2O to H2 at the cathode.
[0041] Example 1
[0042] Assembly and testing of SOEC
[0043] SOEC is actually the reverse process of SOFC. The preparation method of a single cell is the same, but the reactor uses a double-chamber reactor. Its reaction device is composed of a large and a small corundum tube nested together. When H2O is electrolyzed alone, water vapor is introduced into one side of the small tube, and air is introduced into the other side of the large tube; when H2O-C2H6 is co-electrolyzed, water vapor is introduced into one side of the small tube, and C2H6 is introduced into one side of the large tube. The tail gas introduced into the water vapor side needs to be dried and then introduced into the gas chromatograph (GC), and the tail gas introduced into the ethane side is directly introduced into the GC for product analysis. The electrochemical workstation provides a constant DC voltage for the electrolysis process and tests the electrochemical performance.
[0044] Example 2
[0045] Sr 1.95 Microstructure and energy spectrum analysis of FCM0.2 materials
[0046] Figure 1 The SrO2 was obtained by screen printing the electrode paste on both sides of the electrolyte sheet and sintering at 1100℃ for 2h. 1.95 The SEM image of the FCM0.2 symmetric single cell shows that the electrode and electrolyte are tightly bonded, without cracks or delamination. The front and back structures of the electrode are consistent, and the porous three-dimensional structure is conducive to the transmission and diffusion of gas. The CoFe alloy nanoparticles grown in situ at 800℃ in a hydrogen atmosphere for 2h are anchored on the double perovskite matrix, with an average diameter of about 25nm. The strong metal-oxide interface interaction at the nanoscale after the reduction treatment can improve the thermal stability of the nanoparticles at high temperatures and improve the catalytic activity of the electrode.
[0047] Sr 1.95 FCM0.2 performs TEM-EDS mapping element analysis and further magnifies and analyzes a certain nanoparticle, such as Figure 2 As shown, Co and Fe are distributed in the nanoparticles, and a small amount of O element is due to the oxide film produced when the sample is exposed to the air, which will disappear in a high-temperature reducing atmosphere. In order to determine the content of each metal in the CoFe alloy, line scanning and point scanning analysis were performed on a single nanoparticle, where the Fe content was 81.2% and the Co content was 18.8%. The relatively high Fe content may be because the Fe segregation energy is lower than that of Co, and it is easier to precipitate under the same conditions. The CoFe nano-alloy particles formed by in-situ growth can avoid agglomeration and maximize the strong interaction of the metal-oxide interface to improve the electrocatalytic activity.
[0048] In order to analyze the effect of reduced and precipitated nanoparticles on Sr 1.95 The influence of the valence state of FCM0.2 elements was studied by XPS technology on the Sr 1.95 FCM0.2 powder was tested and analyzed.
[0049] Figure 3 a in the figure is Sr before and after reduction 1.95 The XPS spectrum fitting analysis of O1s of FCM0.2 shows that the lattice oxygen O lat. (529.7eV), adsorbed oxygen O 2- / O - (531.4 eV) and hydroxycarbonate species CO3 2- / OH - By fitting and analyzing the peaks of these three oxygen species (see Table 5-1), we found that after reduction, the lattice oxygen O lat. The ratio of O lat. =35.9% reduced to O after reduction lat. =22.0%), and the reduction treatment is beneficial to the lattice oxygen O lat. To absorb oxygen O 2- / O - and hydroxycarbonate species CO3 2- / OH - The transformation helps to improve the transport capacity of oxygen ions and makes the electrocatalytic oxidation of ethane easier.
[0050] Figure 3 b in the middle is Sr before and after restoration 1.95 Analysis of the Co 2p core-level spectrum of FCM0.2 and its fitting results. Before reduction, the Co element is represented by Co 2+ and Co 3+ Valence state exists, no metal Co 0 ; After reduction, a small amount of metallic Co is precipitated, and the Co element is Co 0 、Co 2+ 、Co 3+ There are three valence states, and the fitting peak is located at 794.4eV with high binding energy and Co 0 2p 1 / 2 , 800.8eV and Co 2+ 2p 1 / 2 , 797.1eV and Co 3+ 2p 1 / 2 Correspondingly, the fitting peak is located at 779.4 eV with low binding energy and Co 0 2p 3 / 2 , 785.8eV and Co 2+ 2p 3 / 2 , 782.12eV and Co3+ 2p 3 / 2 Corresponding. After reduction, Co 0 , and Co 3+ The ratio of Co 3+ =53.9%, after reduction Co 3+ =30.2%), and the Co element exists in a lower valence state.
[0051] Figure 3 c in the middle is Sr before and after reduction 1.95 Analysis of the core-level spectrum of Fe 2p of FCM0.2 and its fitting results. Before reduction, Fe element is represented by Fe 2+ and Fe 3+ Valence state exists, no metal Fe 0 ; After reduction, metallic Fe is precipitated, and the Fe element is Fe 0 , Fe 2+ , Fe 3+ The three valence states exist in a mixed state, and the fitting peak is located at 720.6eV with high binding energy and Fe 0 2p 1 / 2 , 723.3eV and Fe 2+ 2p 1 / 2 , 726.4eV and Fe 3+ 2p 1 / 2 Correspondingly, the fitting peak is located at 707.5eV with low binding energy and Fe 0 2p 3 / 2 , 710.2eV and Fe 2+ 2p 3 / 2 , 713.3eV and Fe 3+ 2p 3 / 2 Corresponding. After reduction, Fe 0 , and Fe 3+ The ratio of Fe 3+ =55.5%, after reduction Fe 3+ =51.9%), the element exists in a lower valence state, and the rules before and after reduction are similar to those of Co element.
[0052] Figure 3 d in the middle is Sr before and after restoration 1.95 The core-level spectrum of Mo 3d of FCM0.2 and its fitting results. Regardless of whether it is before or after reduction, the Mo element is Mo 5+ and Mo 6+ These two forms exist, and the fitting peak is located at 234.6eV with high binding energy and Mo 5+ 3d 3 / 2 , 234.9eV and Mo 6+ 3d 5 / 2Correspondingly, the fitting peak is located at 231.4eV with low binding energy and Mo 5+ 3d 3 / 2 , 231.8eV and Mo 6+ 3d 5 / 2 After reduction, Mo 6+ As the proportion decreases, the overall valence of the Mo element decreases.
[0053] After reduction, Sr 1.95 Co appeared in the XPS spectrum of FCM0.2 0 and Fe 0 peak, the precipitation of CoFe nanoparticles from the lattice leads to the partial lattice oxygen O lat. The nanoparticles precipitated in situ in the matrix provide active sites for ethane oxidation and promote the electrochemical oxidation reaction of ethane.
[0054] Example 3
[0055] Sr 1.95 Study on the electrochemical performance of FCM0.2 symmetric structure SOEC for H2O electrolysis
[0056] N2 is used as a carrier gas to pass 20% water vapor into the anode of the electrolytic cell, and dry air is passed into the cathode. The IV curve is the current density-voltage curve obtained by recording the corresponding current density when different voltages are applied to the electrolytic cell. It can reflect the reaction rate of electrolysis and determine the starting potential of electrolysis. Before the electrolytic cell is operated, H2 is introduced at 800℃ for 2 hours for pre-reduction. Under reducing conditions, Sr 1.95 FCM0.2 in-situ precipitates CoFe alloy nanoparticles, anchored on the surface of the double perovskite matrix. At the test temperatures of 750℃, 700℃ and 650℃, a linear scanning method was used to apply a scanning voltage of 0-1.5V to the electrolytic cell, with a scanning speed of 10mV / s. The IV curves obtained are as follows: Figure 4 When the voltage was first applied to the electrolytic cell, the current density was very small, indicating that the electrolysis of H2O had not yet started. When voltages of 0.811V, 0.901V, and 1.033V were applied at 750°C, 700°C, and 650°C, respectively, the current density began to increase significantly, indicating that the electrolysis of H2O had begun. As the temperature increased, the starting voltage of the electrolysis of H2O decreased.
[0057] When a voltage of 1.5 V was applied, the current densities were 1046.3, 632.9, and 344.7 mA cm -2 ; When a voltage of 1.3 V was applied, the current densities were 637.3, 380.4, and 185.8 mA cm -2 ; When a voltage of 1.1 V was applied, the current densities were 297.1, 173.2, and 78.0 mA cm -2; When a voltage of 0.9 V was applied at 750°C, 700°C, and 650°C, the current densities were 87.8, 58.7, and 40.0 mA·cm, respectively. -2 When the same voltage is applied, the current density increases with increasing temperature. This is because the activation polarization of the electrode increases with increasing temperature, and high temperature provides more heat energy for electrolysis, making the electrolysis of H2O easier. At the same temperature, the greater the voltage applied in the range of 0.9V-1.5V, the greater the current density and the faster the electrolysis rate.
[0058] During the SOEC electrolysis process, the reactions occurring on the electrodes are relatively complex, involving multiple steps such as gas adsorption, dissociation, diffusion, and charge and ion transfer in the electrodes. The electrochemical impedance spectroscopy test is used to study the effects of each step on the electrolysis reaction.
[0059] The intersection of the AC impedance spectrum and the x-axis on the left is the ohmic resistance, which is mainly generated by the electrolyte LSGM. The difference between the AC impedance spectrum and the x-axis intercept is the total polarization impedance R p The impedance spectrum is mainly composed of high-frequency and low-frequency parts. The high-frequency part represents the activation polarization impedance, which is related to the charge transfer process and the transmission process of electrons and ions in the electrode; the low-frequency part represents the concentration polarization impedance, which is related to the transmission, adsorption, dissociation and diffusion of gas in the electrode.
[0060] The test frequency range is 1000kHz-0.01Hz, and the disturbance amplitude is 50mV.
[0061] Figure 5 Figure a is the AC impedance spectrum of the electrolytic cell at different temperatures when the potential is constant at 1.3 V. The ohmic resistance at 750°C, 700°C, and 650°C is 0.2, 0.3, and 0.5Ω·cm, respectively. 2 , which is mainly generated by the electrolyte LSGM, decreases with increasing temperature because the oxygen ion conductivity of LSGM increases with increasing temperature. The total polarization impedance R at 750℃, 700℃ and 650℃ p 0.2, 0.4, 0.8 Ω·cm respectively 2 As the temperature increases, the electrode catalytic activity increases, the activation polarization impedance decreases, and the total polarization impedance R p Gradually reducing and increasing the temperature can improve the electrolytic performance of the electrolytic cell.
[0062] Figure 5 Figure b is the AC impedance spectrum of the electrolytic cell at 700°C with different voltages applied. The ohmic resistance remains unchanged under different voltages, indicating that the ionic conductivity of the electrolyte does not change significantly with the voltage change. However, the total polarization impedance R pIt decreases with the increase of applied voltage. This may be because increasing the electrolysis voltage will accelerate the transfer of charge in the electrode, thereby improving the activation polarization of the electrode and making the total R p It decreases, indicating that the increase of electrolysis voltage is conducive to the electrolysis reaction.
[0063] The activation polarization process of the electrode can be improved by increasing the temperature or the applied voltage, thereby reducing the total polarization resistance R p , so that the electrochemical performance of the electrolytic cell is improved.
[0064] Stability is one of the important indicators for evaluating the performance of SOEC. Figure 6 It is Sr. 1.95 Short-term stability test of SOEC with FCM0.2 symmetrical structure at 700℃ with different electrolysis voltages. The current densities were 38.7, 171.3, 293.9 and 594.2 mA·cm at 0.9V, 1.1V, 1.3V and 1.5V for 30 minutes respectively. -2 During the operation, the current density does not change much with time and there is no obvious attenuation. The electrolytic cell operates smoothly at various electrolysis voltages.
[0065] The working conditions of H2O electrolysis are high temperature and high humidity, and the electrode materials are prone to agglomeration and loss of activity, so it is necessary to evaluate the long-term stability to further verify the performance of SOEC. Then, the electrolysis voltage of 1.1V was applied at 700℃ for 20 hours, and the current density was 210.0mA·cm -2 , the curve of current density and time is stable and no attenuation occurs. Figure 7 is the Sr observed after the long-term stability test 1.95 The cross-sectional SEM image of the FCM0.2 electrode shows that the electrode and the electrolyte are still tightly bonded, with no cracks or delamination. When the electrode surface is magnified, its structure remains loose and porous, without agglomeration. The integrity of the electrode structure and the electrolytic cell structure is a prerequisite for good long-term stability.
[0066] Example 4
[0067] Sr 1.95 Study on the electrochemical performance of FCM0.2 symmetric SOEC co-electrolysis of H2O-C2H6
[0068] N2 is used as a carrier gas to pass 20% water vapor into the cathode of the electrolytic cell, and ethane is passed into the anode. The reaction at the cathode is: O 2- The oxygen ion conductor electrolyte LSGM is transported to the anode, and the reaction occurring at the anode is:
[0069] Before the electrolytic cell was operated, H2 was introduced at 800℃ for 2 hours for pre-reduction. 1.95 FCM0.2 in situ precipitates CoFe alloy nanoparticles, anchored on the surface of the double perovskite matrix, and metal nanoparticles directly embedded in the porous oxide show better high-temperature stability and resistance to carbon deposition, which may be due to the strong metal-oxide interaction at the unique nanoscale interface structure. In addition, the strong interface interaction is also very conducive to the transfer of oxygen species, especially the oxygen species O required for ethane oxidation. 2- It is expected that these reactive oxygen species can electrochemically activate and oxidize C2H6 in situ, and the reactive oxygen species present at the metal oxide interface of the cathode can also remove carbon deposits.
[0070] At the test temperatures of 750°C, 700°C and 650°C, a linear scan method was used to apply a scan voltage of 0-1.5V to the electrolytic cell at a scan rate of 10mV / s. The IV curves obtained are as follows: Figure 8 When voltages above 0.689 V, 0.791 V and 1.014 V were applied at 750°C, 700°C and 650°C, respectively, the current density began to increase significantly, indicating that the co-electrolysis of H2O-C2H6 reaction began, and as the temperature increased, the starting voltage of the co-electrolysis of H2O-C2H6 decreased.
[0071] When a voltage of 1.5 V was applied, the current densities were 4565.8, 1002.8, and 347.2 mA·cm -2 ; When a voltage of 1.3 V was applied, the current densities were 3033.5, 588.6, and 191.1 mA cm -2 ; When a voltage of 1.1 V was applied, the current densities were 1807.8, 382.3, and 82.6 mA·cm -2 ; When a voltage of 0.9 V was applied at 750°C, 700°C, and 650°C, the current densities were 945.3, 278.1, and 51.7 mA·cm, respectively. -2 When the same voltage is applied, the current density increases with increasing temperature. This is because the activation polarization of the electrode increases with increasing temperature, and high temperature provides more heat energy for electrolysis, making the electrolysis of H2O easier. At the same temperature, the greater the voltage applied in the range of 0.9V-1.5V, the greater the current density and the faster the electrolysis rate.
[0072] Fig. 9This is a comparison of the IV curves of co-electrolysis of H2O-C2H6 and single electrolysis of H2O. At the same temperature, the starting electrolysis voltage of co-electrolysis of H2O-C2H6 (0.689V) is lower than that of single electrolysis of H2O (0.811V). The simultaneous electrolysis of H2O and C2H6 will accelerate the transmission of oxygen ions in the electrolyte, making the electrolysis reaction easier. At 700℃, the same electrolysis voltage is applied, and the current density of co-electrolysis (4565.8mA·cm -2 ) than single electrolysis (1046.3mA·cm -2 ) is much larger, and the electrolysis reaction rate is faster. The advantage of co-electrolysis of H2O-C2H6 is that the O produced by cathode electrolysis of H2O 2- The oxygen ion electrolyte sheet LSGM continuously goes to the anode to selectively oxidize C2H6 to generate C2H4. The active oxygen species O 2- The carbon deposits produced on the porous anode can also be oxidized and removed, thereby improving the resistance to carbon deposition during the cracking process of C2H6.
[0073] Through electrochemical impedance spectroscopy testing, the effects of gas adsorption, dissociation, diffusion, and charge and ion transfer in the electrode on the electrolysis reaction are studied.
[0074] The test frequency range is 1000kHz-0.01Hz, and the disturbance amplitude is 50mV.
[0075] Fig.10 a is the AC impedance spectrum of the electrolytic cell at different temperatures when the potential is constant at 1.3 V. The ohmic resistance at 750°C, 700°C and 650°C is 0.39, 0.40 and 0.59 Ω·cm respectively. 2 , which is mainly generated by the electrolyte LSGM, and decreases slightly with increasing temperature because the oxygen ion conductivity of LSGM increases with increasing temperature. The total polarization impedance R at 750℃, 700℃ and 650℃ p 0.30, 0.40, 1.00Ω·cm respectively 2 As the temperature increases, the electrode catalytic activity increases, the activation polarization impedance decreases, and the total polarization impedance R p Gradually reducing and increasing the temperature can improve the electrolytic performance of the electrolytic cell.
[0076] Fig.10 Figure b is the AC impedance spectrum of the electrolytic cell at 700°C with different voltages applied. The ohmic resistance remains unchanged under different voltages, indicating that the ionic conductivity of the electrolyte does not change significantly with the voltage change. The total polarization impedance R when the applied voltage is 1.5V and 1.3V pThere is little difference, and the activation polarization degree of the electrode is similar. At 1.0V, the impedance in the low-frequency region has no intersection with the x-axis. When the applied voltage is low, it affects the diffusion of the gas and the concentration polarization is large. Increasing the electrolysis voltage will accelerate the transfer of charge in the electrode to improve the electrode activation polarization, and can also eliminate the influence of concentration polarization, thereby improving the electrode activation polarization and making the total R p The decrease of electrolysis voltage can promote the electrolysis reaction.
[0077] By increasing the temperature or the applied voltage, the activation polarization and concentration polarization processes of the electrode can be improved, thereby reducing the total polarization impedance R p , improving the electrochemical performance of the electrolytic cell.
[0078] The present invention converts Sr 1.95 The reaction products of FCM0.2 symmetric structure SOEC co-electrolysis of H2O-C2H6 were introduced into gas chromatography (GC), and the ethane conversion rate and ethylene selectivity were obtained by calculating the corresponding product peak area, which was used to measure the ability of electrochemical ethane oxidation as co-electrolysis of H2O-C2H6. Fig.11 As shown, the ethane conversion rate gradually increases with increasing temperature, reaching 35.7% when 1.3V is applied at 750℃; because ethane oxidation will produce more by-products at high temperature, the ethylene selectivity decreases slightly with increasing temperature.
[0079] Fig.12 a in the sentence is Sr 1.95 The short-term stability test of FCM0.2 symmetrical SOEC was conducted at 700℃ with different voltages for co-electrolysis of H2O-C2H6. The current densities were 66.3, 166.2, 422.7 and 628.8 mA·cm at 0.9V, 1.1V, 1.3V and 1.5V for 30 minutes respectively. -2 , the current density did not decay significantly during operation, and the electrolytic cell operated smoothly at various electrolysis voltages. Further, when the SOEC was operated at 700℃ and 1.1V for 20 hours, the current density of the SOEC did not change much over time, and the operation was stable.
[0080] The electrodes were observed using SEM after running for 20 hours. Fig.13 As shown in middle a, we can see that the porous electrode still has a clear microstructure, no obvious carbon deposits are observed, and no obvious carbon characteristic peaks appear in the subsequent Raman infrared spectrum test.
[0081] Agglomeration and carbon deposition of nanoparticles can lead to performance degradation, so the long-term stability of high-temperature C2H6 conversion is a major challenge. In the co-electrolysis of H2O-C2H6, CoFe nanoparticles are precipitated in situ in the double perovskite matrix, and the nanoscale metal-oxide interface can prevent nanoparticle agglomeration caused by reduced surface energy, thereby improving long-term stability and redox stability. For C2H6 conversion, carbon deposition is another factor that leads to severe deactivation of metal nanoparticles, which is usually produced during the oxidation of C2H6. As shown in the figure, after running at 700℃ for 20 hours at an applied voltage of 0.7V, the SOEC still maintains good stability. The improvement of anti-carbon deposition performance at high temperature is, on the one hand, the strong interaction at the precipitated metal-oxide interface produces typical interfacial charge transfer. On the other hand, when co-electrolyzing H2O-C2H6, the cathode electrolysis H2O reaction continuously provides oxygen species O for the anode electrolysis C2H6 reaction. 2- , a steady stream of reactive oxygen species O 2- It can also remove carbon deposits generated on the porous anode, thereby improving the resistance to carbon deposition during C2H6 oxidation.
[0082] In summary, the present invention selects the double perovskite material Sr with the best electrochemical performance 1.95 Fe 1.3 Co 0.2 Mo 0.5 O 6-δ (Sr 1.95 FCM0.2) is used as a symmetrical electrode of the low-energy hydrogen production and co-production of olefins solid oxide electrolysis cell SOEC. A series of characterization tests were carried out on single electrolysis of H2O and co-electrolysis of H2O-C2H6 to explore the influence of the metal-oxide interface formed by the precipitation of alloy nanoparticles in the double perovskite matrix on the electrolysis reaction in a reducing atmosphere. The stability test and analysis of the co-electrolysis of H2O-C2H6 were carried out, and the following conclusions were obtained:
[0083] By pre-reduction treatment before the electrolytic cell test, the CoFe alloy nanoparticles precipitated from the double perovskite matrix in the reducing atmosphere formed a metal-oxide interface, which is very suitable for producing the oxygen species required for ethane oxidation. It can not only improve the activation activity of ethane conversion, but also improve the stability and resistance to carbon deposition. After the electrolytic cell worked for 20 hours, the performance did not show obvious attenuation, the electrode microstructure remained intact, and there was no obvious carbon deposition phenomenon; electrolysis was carried out through the cathode At the same time, electrolysis is carried out at the anode The co-electrolysis reaction successfully achieved the production of C2H4 from C2H6 at the anode and H2 from H2O at the cathode. This ingeniously designed co-electrolysis of H2O-C2H6 has a higher current density than single electrolysis of H2O, reaching 4565.8 mA cm at 750 °C and 1.5 V. -2, the electrolysis reaction is easier to proceed; by utilizing the oxygen ion conductor SOEC, the oxygen ion conductor continuously transmits the active oxygen species produced by the cathode to the anode, which can not only selectively electrochemically activate and oxidize C2H6 to produce C2H4, with an ethylene selectivity of up to 98.9%, but also oxidize and remove the carbon deposits produced on the porous anode. There is no obvious characteristic peak of carbon in the infrared Raman spectrum, thereby improving the selectivity and anti-carbon deposition ability in the C2H6 conversion process.
[0084] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A low-energy consumption solid oxide electrolysis cell for producing hydrogen and co-producing olefins, characterized in that: The invention comprises a solid electrolyte and an anode and a cathode located on both sides of the solid electrolyte, wherein the materials of the anode and the cathode are both Sr 1.95 Fe 1.3 Co 0.2 Mo 0.5 O 6-δ ; The method for using the low-energy consumption hydrogen production and co-production of olefins solid oxide electrolysis cell comprises: introducing water vapor into the cathode and introducing ethane into the anode.
2. The low-energy consumption hydrogen production and co-production of olefins solid oxide electrolysis cell according to claim 1, characterized in that: The material of the solid electrolyte is LSGM.
3. A method for preparing a low-energy consumption hydrogen production and co-production of olefins solid oxide electrolytic cell as claimed in claim 1, characterized in that: Includes steps: An anode and a cathode are provided, wherein the materials of the anode and the cathode are both Sr 1.95 Fe 1.3 Co 0.2 Mo 0.5 O 6-δ ; The anode and cathode are printed on both sides of the solid electrolyte, and the anode and cathode are connected via a wire to obtain the low-energy consumption hydrogen production and co-production of olefins solid oxide electrolysis cell.
4. The method for preparing a solid oxide electrolytic cell for producing hydrogen and olefins with low energy consumption according to claim 3, characterized in that: The Sr 1.95 Fe 1.3 Co 0.2 Mo 0.5 O 6-δ The preparation comprises the steps of: Co(NO3)2, Sr(NO3)2, Fe(NO3)3·9H2O and (NH4)6Mo7O were added according to the set stoichiometric ratio. 24 4H2O is dissolved in an aqueous solution containing nitric acid to completely dissolve the nitric acid to obtain a first mixed solution; According to n (CA) :n (EDTA) :n (totalions) =1.5:1:1 ratio, sequentially adding citric acid and ethylenediaminetetraacetic acid to the first mixed solution, stirring evenly, to obtain a second mixed solution; Adding aqueous ammonia to the second mixed solution, adjusting the pH value of the second mixed solution to 7-7.5, and completely dissolving the ethylenediaminetetraacetic acid to obtain a third mixed solution; The third mixed solution is stirred to form a metal complex solution, and then heated to dryness at 200° C. until burned, and the precursor is collected; The precursor is moved into a crucible for calcination to obtain the Sr 1.95 Fe 1.3 Co 0.2 Mo 0.5 O 6-δ .